Characterizing non-thermal equilibrium contact binaries. Issue 1 (19th September 2022) - Wang, Z H; Zhu, L Y; Yuan, K
ABSTRACT: Formation and evolution of marginal contact binaries with larger temperature difference between their two components remain inexplicable to date. To get a better understanding of the nature of such population we investigate on an individual, NSVS 7358116, by analysing observational data obtained from ground-based and space-based telescopes. It is found that NSVS 7358116 is a marginal contact totally eclipsing binary with a small fill-out factor by 3 per cent but large temperature difference by 2000 K or t-ratio by 0.3. This suggests that its two components are in poor thermal contact. By collecting all available targets in literature, we compiled a table of 80 non-thermal equilibrium contact binaries (nTCBs) including 39 STRONG t-ratio samples and 41 WEAK t-ratio samples . We performed statistical distribution analysis on physical parameters which reveals that STRONG t-ratio samples will evolve to WEAK t-ratio samples through heat and mass transfer along with angular momentum loss, meanwhile thickening their common envelop. This current investigation is acted as only an appetizer, because more exploration on nTCBs and its evolutionary connection with related populations will follow.